Student Entrepreneurial Interest Analysis Based on the Effect of Self-Efficacy and Social Media Utilization - Sembiring, Lenny Dermawan; Setyawati, Amelia; Hanika, Ita Musfirowati; Lie, Darwin; Sudirman, Acai (International Journal of Scientific Research and Management (IJSRM), 2022)
This study examines the effect of self-efficacy and social media utilization on student entrepreneurial interest. The data collected in this study are quantitative data using a quantitative approach. The population in this study were university students in Pematang Siantar City, with a sample of 100 students determined by convenience sampling. Data analysis used an instrument test, normality test, regression test, hypothesis test and correlation test, and the coefficient of determination. The results showed that self-efficacy and social media utilization positively and significantly affected student entrepreneurial interest. The conclusion of the study confirms the existence of self-efficacy is believed to be able to increase self-confidence for students to start a new business. Self-efficacy representatives, such as the spirit not to give up easily and the willingness to work hard, are believed to be able to encourage students' interest in entrepreneurship. Furthermore, by using social media, young entrepreneurs such as students will increase their interest in starting a business because they no longer need a physical building to display their wares, reducing business operational costs